Socio-Legal Review Of The Environmental Approval For The Construction Of Water Tank Of Regional Water Company Tirta Asasta Depok City - Yusron, Muhammad; Al Afghani, M. Mova; Ratnawaty, Latifah (JURNAL MAHASISWA YUSTISI, 2025)
The environment, as a gift from God Almighty for the people and nation of Indonesia, is a space for life in all its aspects and dimensions in accordance with the insight of the archipelago. Article 67 of Law No. 32/2009 on Environmental Protection and Management states that “Everyone is obliged to maintain the preservation of environmental functions and control pollution and/or environmental damage”. In Indonesia, environmental issues are a problem in almost all regions. Based on data from the website of the Ministry of Environment and Forestry of the Republic of Indonesia, the Directorate of Environmental Dispute Resolution (PSLH) throughout 2023 has pursued 11 environmental cases that were successfully resolved through the court and 19 cases that were successfully resolved out of court. One of the cases occurred in the Depok City area in 2023, namely the construction of a water tank with a capacity of 10 million liters initiated by the Tirta Asasta Regional Water Supply Company of Depok City. The water tank was built to fulfill the supply of clean water, but the problem was that the construction of the water tank was carried out in a densely populated area adjacent to a number of schools and houses of worship. In addition, in the construction process, residents mentioned that the project implementer did not socialize the project to residents and although it already has a building construction permit (IMB), this project only has Environmental Approval in the form of an Environmental Management Statement Letter (SPPL). Based on this, the residents rejected the construction of the water tank and sued the licensing of the project to the Bandung State Administrative Court. The purpose of this research is to find out the regulations regulated by law regarding the provisions for issuing Environmental Approval and to find out the implementation of Environmental Approval and the solutions that can be provided to local residents if there is a problem with the water tank building of PDAM Tirta Asasta Depok City.